Automatic data collection for incoherent scatter complex - Kozlov, S. S. (НТУ "ХПІ", 2014)
The creation of the automated data collection system for incoherent scatter complex is justified. The main part of the parameters influencing the control action was considered. The simplified implementation of automated data collection system is presented.

Обґрунтовано створення автоматизованої системи збору інформації для комплексу некогерентного розсіяння. Розглянуто основний склад параметрів, що впливає на керуючий вплив. Представлена спрощена реалізація автоматизованої системи збору інформації.
Keywords: automated data acquisition system; control action; incoherent scatter radar; program product; автоматизована система збору інформації; керуючий вплив; радар некогерентного розсіяння; програмний продукт